فعالية استراتيجية التعلم التعاوني في تدريس الرياضيات - باللموشي, عبد الرزاق; بوعامر أحمد, زين الدين (University of Eloued جامعة الوادي, 2017)
لقد ظهرت استراتيجيات حديثة في تدريس الرياضيات خصصت للتلميذ فيها دورا بارزا من حيث فاعليته وتفاعله، ومن هذه الاستراتيجيات استراتيجية التعلم التعاوني التي لها ميزات عديدة ليس فقط في التحصيل، ولكن في الجوانب الأخرى من التعليم مثل: الجوانب الانفعالية وتنمية المهارات والتعاون والاتجاه نحو المدرسة والاتجاه نحو الآخرين وتنمية التفكير الابتكاري والقدرة على حل المشكلات الرياضية من خلال الربط بين المستويات الواقعية والمجردة للتعليم لتمكينهم من فهم الرموز والمعادلات الرياضية والكسور وغيرها من المفاهيم الرياضية. Abstract Modern strategies have emerged in the teaching of mathematics; the student has become a prominent role, in terms of his effectiveness and interaction, From these strategies: there is cooperative learning strategy, which has many advantages, not only in the collection, but in other aspects of education, such as: emotional aspects and development of skills and Cooperation and the trend towards the school and the trend towards others and the development of innovative thinking and the ability to solve mathematical problems by linking realistic and mere levels of education to enable them to understand the mathematical symbols and equations and other mathematical concepts
The effectiveness of Cooperative learning strategy in the teaching of mathematics
مجلة البحوث والدراسات المجلد 14 العدد 01 جامعة الوادي
Keywords: الاستراتيجية - التعلم التعاوني – الرياضيات; strategy - cooperative learning - mathematics